Human genealogy reveals a selective advantage to moderate fecundity - Oded Galor; Marc P. B. Klemp (Brown University, Department of Economics, 2019)
This research presents the first evidence that moderate fecundity had maximized long-run reproductive success in the human population. Using a reconstructed genealogy for nearly half a million individuals in Quebec during the 1608-1800 period, we find that while a high fecundity was associated with a larger number of children, perhaps paradoxically, a moderate fecundity had maximized the number of descendants after several generations. Moreover, the finding suggests that the level of fecundity that maximized long-run reproductive success was above the population average, indicating that natural selection had decreased the level of fecundity in the population over this period. This evolutionary process may have contributed to the onset of the demographic transition and thus to the evolution of societies to an era of sustained economic growth.
Keywords: J10; N30; O10; 330; Demography; Evolution; Human Capital Formation; Natural Selection; Fecundity; Quantity-Quality Trade-Off; Long-Run Reproductive Success; Economic Growth